The larval scaffold controls fascicle number but is not required for formation of the dorsolongitudinal flight muscles in Manduca sexta. (May 2022) - Ludwig, J. Clark; Aonuma, Hitoshi; Trimmer, Barry
Abstract: During metamorphosis, the dorsolongitudinal flight muscles (DLMs) of both the moth Manduca sexta and the fly Drosophila melanogaster develop from the remnants of larval muscles called larval scaffolds. Although this developmental program has been conserved across highly disparate taxa, the role of the larval scaffold remains unclear. Ablation experiments have demonstrated that the Drosophila DLM does not require the scaffold, but the resulting de novo muscles vary highly in fiber number, and their functional characteristics were not examined. To address this question in Manduca, we have surgically ablated the DLM precursors in Manduca sexta larvae and assayed the resulting DLMs in pharate adults using X-ray micro-CT and phalloidin histology. Following ablation, animals were able to form de novo DLMs with normal myofibril alignment, but these muscles had an altered shape and highly variable number of fascicles. Our results suggest that the larval scaffold is not required for DLM development in Manduca sexta, but appears to define the number of fascicles in the adult muscle, as previously found in Drosophila . Additionally, our ablated animals were able to generate flight, further suggesting that the use of a larval scaffold is a modification on the more ancestral myogenesis program. Highlights: Larval precursors are not required for formation of dorsolongitudinal flight muscles. Larval scaffolds do not control muscle size or sarcomere alignment. Larval scaffolds may control fascicle number.